Oncogenic activity of BIRC2 and BIRC3 mutants independent of nuclear factor‐κB‐activating potential. Issue 9 (14th July 2015) - Yamato, Azusa; Soda, Manabu; Ueno, Toshihide; Kojima, Shinya; Sonehara, Kyuto; Kawazu, Masahito; Sai, Eirin; Yamashita, Yoshihiro; Nagase, Takahide; Mano, Hiroyuki
<x xml:space="preserve">Abstract</x> BIRC2 and BIRC3 are closely related members of the inhibitor of apoptosis (IAP) family of proteins and play pivotal roles in regulation of nuclear factor‐κB (NF‐κB) signaling and apoptosis. Copy number loss for and somatic mutation of BIRC2 and BIRC3 have been frequently detected in lymphoid malignancies, with such genetic alterations being thought to contribute to carcinogenesis through activation of the noncanonical NF‐κB signaling pathway. Here we show that BIRC2 and BIRC3 mutations are also present in a wide range of epithelial tumors and that most such nonsense or frameshift mutations confer direct transforming potential. This oncogenic function of BIRC2/3 mutants is largely independent of their ability to activate NF‐κB signaling. Rather, all of the transforming mutants lack an intact RING finger domain, with loss of ubiquitin ligase activity being essential for transformation irrespective of NF‐κB regulation. The serine‐threonine kinase NIK was found to be an important, but not exclusive, mediator of BIRC2/3‐driven carcinogenesis, although this function was independent of NF‐κB activation. Our data thus suggest that, in addition to the BIRC2/3–NIK–NF‐κB signaling pathway, BIRC2/3–NIK signaling targets effectors other than NF‐κB and thereby contributes directly to carcinogenesis. Identification of these effectors may provide a basis for the development of targeted agents for the treatment of lymphoid malignancies and other cancers with BIRC2/3 alterations.